A case of uveoscleral mucosa-associated lymphoid tissue lymphoma with secondary angle-closure glaucoma - Mizuho Mitamura; Satoru Kase; Yuka Suimon; Kenjiro Kato; Hiromi Kanno-Okada; Susumu Ishida (BMC Ophthalmology)
Abstract Background/Aim Mucosa-associated lymphoid tissue (MALT) lymphomas occur in not only the ocular adnexa, but rarely in the sclera or uvea. Histopathological confirmation contributes to a better understanding of the pathogenesis and treatment. We report a case of uveoscleral MALT lymphoma with angle-closure glaucoma. Case report A 73-year-old man was referred to our hospital for a detailed examination of a choroidal mass oculus sinister (OS). At the initial examination, best-corrected visual acuity (BCVA) was 0.4 OS, intraocular pressure was 37 mmHg OS, the left eye had a narrow angle with anterior chamber inflammation. Optical coherence tomography (OCT) showed marked choroidal elevation. Anterior segment OCT showed tumor invasion into the inferior angle and ultrasound B-mode echography demonstrated choroidal thickening and a banded hypoechoic area posterior to the eye. Magnetic resonance imaging showed isointensity in the tumor on heterogeneous enhancement on gadolinium contrast-T1WI. A tumor biopsy of the left sclera was performed one month after the initial visit. Based on pathological findings, he was diagnosed with uveoscleral MALT lymphoma. Two months after the initial visit, left eye irradiation was performed. Nine months after the initial visit, the tumor was in remission with open angle. Conclusion Angle-closure glaucoma caused by the uveoscleral MALT lymphoma was treated with radiotherapy, leading to IOP normalization as well as tumor remission.